Application of the workflow management system in electronic commerce: a case study. (19th July 2005) - Ngai, Eric W.T.; Leung, C.H.; Wong, Y.C.
Electronic commerce (e-commerce) applications are developed to allow companies to communicate with their partners, suppliers, and consumers on the internet. The migration from traditional business to e-commerce requires fundamental changes in business operational systems. It is not sufficient to focus on the development of web-based interfaces only. The front-end of a system for e-commerce should be supported by the back-end infrastructure. A Workflow Management System (WFMS) is important for linking front-end and back-end applications to automate business processes. In this paper, a generic model of a WFMS in e-commerce is proposed. Based on the proposed model, a specific WFMS model was developed and implemented in a company for a case study. The case study illustrates and highlights the benefits and advantages of the system. The user survey results from the case study showed that the users responded positively to the WFMS.